2010
DOI: 10.1182/blood.v116.21.208.208
|View full text |Cite
|
Sign up to set email alerts
|

An Ongoing Phase 3 Study of Bosutinib (SKI-606) Versus Imatinib In Patients with Newly Diagnosed Chronic Phase Chronic Myeloid Leukemia

Abstract: 208 Bosutinib is an orally bioavailable dual Src/Abl tyrosine kinase inhibitor (TKI), with minimal inhibitory activity against PDGFR or c-kit. In a phase 2 study, bosutinib demonstrated activity in patients with Philadelphia chromosome–positive (Ph+) chronic phase (CP) chronic myeloid leukemia (CML) in the second- and third-line treatment settings (Cortes JE, et al. ASCO 2010, Abstract #6502; Khoury JH, et al. ASCO 2010, Abstract #6514), as well as in patients with advanced Ph+ leukemias (Gambac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…A total of 365 potentially relevant references were identified by the electronic search, of which a total of six trials, reported in 20 published papers and conference abstracts, met the inclusion criteria and were pooled in meta-analysis. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Figure 1 depicts the results of the search strategy and study selection.…”
Section: Search Results and Study Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 365 potentially relevant references were identified by the electronic search, of which a total of six trials, reported in 20 published papers and conference abstracts, met the inclusion criteria and were pooled in meta-analysis. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Figure 1 depicts the results of the search strategy and study selection.…”
Section: Search Results and Study Descriptionmentioning
confidence: 99%
“…Both trials had a maximum follow-up period of 5 years. Four publica-tions and abstracts reported on bosutinib versus imatinib in newly diagnosed CML patients, referred to as BELA, [28][29][30][31] with a median reported follow-up period of 19 months; the trial is still ongoing. Two conference abstracts reported on ponatinib versus imatinib in newly diagnosed CML patients, referred to as EPIC 32,33 ; EPIC was terminated early after a median of 3 months and a follow-up time of 5 months, due to the observation of vascular events in long-term follow-up of phase II trial evaluating ponatinib 37 ; therefore, data of this study were not included in the pooled MTC, but a direct comparison was conducted comparing ponatinib to imatinib.…”
Section: Search Results and Study Descriptionmentioning
confidence: 99%
“…The preliminary results from a frontline randomized Phase 3 study comparing the activity and toxicity of imatinib were presented at the 52nd ASH meeting [10]. The study enrolled 502 newly diagnosed patients with CML‐CP.…”
Section: Bosutinib As Frontline Therapy For Patients With Cml‐cpmentioning
confidence: 99%
“…In this regard, the use of second‐generation TKIs (i.e., nilotinib, dasatinib, bosutinib) as frontline therapy has led to an increase in the number of patients capable of achieving CCyR during the first year of therapy. The activity of these agents as frontline therapy for patients with CML‐CP has been tested in a series of ongoing randomized, multicenter: nilotinib (ENESTnd), dasatinib (DASISION and Intergroup Trial SO325), and bosutinib [8–10].…”
mentioning
confidence: 99%
“…Bosutinib, a dual Src/ABL TKI, displayed activity in patients previously treated with imatinib [14–16]. In the BELA (Bosutinib Efficacy and Safety in Chronic Myeloid Leukemia) study, patients with newly diagnosed CML‐CP were randomized to bosutinib 500 mg daily ( n = 250) or imatinib 400 mg daily ( n = 252).…”
Section: No 3: An Ongoing Phase 3 Study Of Bosutinib (Ski‐606) Versumentioning
confidence: 99%